The Impacts of Model Project Based Learning Concern on Edupreneurship Towards Learning Outcomes in Science Subjects - Widyaningtyas, Reny; Wiyanto, Wiyanto; Nuswowati, Murbangun (Universitas Negeri Semarang, 2021)
In this research, the students' science learning outcomes that have not yet achieved completeness. Learning model can facilitate students to learn optimally is the project-based learning (PjBL) model according to edupreneurship. The model is driven by creativity and innovation of 21st century skills. This research conducted to; 1) analyze the effect of the model on students' curiosity; 2) analyze the effect of model on students' science knowledge outcomes and 3) analyze the effect of the model on science process skills. This research method is a quasy experimental with a nonequivalent control group design. The control class should be used project-based learning model and the project-based learning model according to edupreneurship was used experimental class. The subjects of this study were 177 students with purposive sampling technique. Data in the form of learning outcomes are collected through observation, tests, and documentation. The conclutions of the study is the model effective to use and affeted toward outcomes learning of students’ coriusity aspect on science subject. The model has not been affecting the students’ learning outcomes of knowledge on science subject. The model efefctively to use and influences learning outcomes about students’ scientific proceeding skill on learning science subject.